Are underground organs able to store water and nutrients? A study case in non-arboreal species from the Brazilian Cerrado - da Silva, Bianca Helena Porfírio [UNESP]; Rossatto, Davi Rodrigo [UNESP] (Springer Nature, 2019)
In seasonal systems, species have specific traits to deal with water shortage. This is the case for plants in Neotropical savannas, where the dry season can endure 3 to 5 months without rain. Ecophysiological strategies to deal with the dry period are well known for savanna trees, however little is known for non-arboreal species such herbs and subshrubs concerning their water use strategies. In this study we analyzed traits related to water and nutrient storage in underground organs and leaves of non-arboreal Cerrado (Neotropical savanna of Brazil) plants. We hypothesized that underground organs are able to retain water and nutrients allowing non-arboreal plants to resprout even during water shortage. We measured wood density (WD) and saturated water content (SWC) in underground organs of 15 species differing in their growth form (5 herbs, 5 subshrubs and 5 shrubs). We also measured macronutrients concentration in underground organs and leaves of these species. We tested relationships between WD and SWC and between concentrations of underground and leaf macronutrients. We found that WD and SWC are negatively related, and that herbs showed the lowest WD, but the highest capacity to store water (higher SWC). We did not find any significant difference concerning nutrient content in underground organs and leaves among the growth forms; however, the leaf nutrient content was positively affected by the nutrient content in underground organs for N, K and Ca. We conclude that underground organs may have an important role on storing water and nutrients in savanna herbaceous species, which will promote their resprout even during the dry period.
Keywords: Cerrado; Herbs; Macronutrients; Water storage; Wood density